2004
DOI: 10.1111/j.1365-2249.2004.02559.x
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of lupus manifestations by a peptide based on the complementarity determining region 1 of an autoantibody in severe combined immunodeficient (SCID) mice engrafted with peripheral blood lymphocytes of systemic lupus erythematosus (SLE) patients

Abstract: SUMMARYA peptide based on the complementarity determining region (CDR)1 of a human monoclonal anti-DNA autoantibody (hCDR1) was shown to either prevent or treat an already established murine lupus in systemic lupus erythematosus (SLE)-prone mice or in mice with induced experimental SLE. The present study was undertaken to determine the therapeutic potential of hCDR1 in a model of lupus in severe combined immunodeficient (SCID) mice engrafted with peripheral blood lymphocytes (PBL) of patients with SLE. To this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Moreover, we were able to establish a human model of SLE by transferring PBMC of lupus patients into severe combined immunodeficient (SCID) mice [21]. Treatment with hCDR1 ameliorated serologic (human anti-DNA antibodies) and clinical lupus-related manifestations in the latter SCID model of human SLE [22]. In view of the various immunomodulatory effects of hCDR1 in the murine models of lupus, it was of interest to determine the effects of the peptide on PBMC obtained from SLE patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we were able to establish a human model of SLE by transferring PBMC of lupus patients into severe combined immunodeficient (SCID) mice [21]. Treatment with hCDR1 ameliorated serologic (human anti-DNA antibodies) and clinical lupus-related manifestations in the latter SCID model of human SLE [22]. In view of the various immunomodulatory effects of hCDR1 in the murine models of lupus, it was of interest to determine the effects of the peptide on PBMC obtained from SLE patients.…”
Section: Introductionmentioning
confidence: 99%
“…Further on, the successfully humanized SCID mice develop many symptoms of the human lupus (anti-dsDNA antibodies, skin lesions, proteinuria, and glomerulonephritis, etc.) and are a suitable model to investigate the efficiency of therapeutic B-cell depletion [39][40][41]. In the present study, we established a humanized SCID model to investigate the effect of the treatment with DNA-like chimera on the pathogenesis of human SLE.…”
mentioning
confidence: 99%
“…Further studies confirmed the importance of the idiotypic epitopes that later on were identified as the sequence of amino-acid peptides residing in the antigen binding site (CDR) regions 1 or 3 [24][25][26].…”
Section: From Induction To Therapymentioning
confidence: 76%